Influence of industrial by-product sulfur powder on properties of cement-based composites for sustainable infrastructures. (27th February 2023) - Zheng, Suining; Lu, Xiaosong; Zhao, Jian; He, Rui; Chen, Huaxin; Geng, Yao
Highlights: An appropriate amount of MSP and NSP improves the durability of cement-based composites. MSP enhances the interfacial adhesion between SP and cement matrix. MSP reduces the rate of hydration release rate and refines the pore size distribution. MSP and NSP play a role in filling pores and hinder the development of micro-cracks. Abstract: The use of industrial by-products has attracted much attention globally in recent years because of the improved durability and sustainability of cement-based composites. To promote the application of sulfur powder (SP) in cement-based composites, a new hydrophilic modified sulfur powder (MSP) was prepared in this paper. The effects of unmodified sulfur powder (NSP) and MSP on workability, strength, permeability, dry shrinkage, and frost resistance of cement-based composites were thoroughly studied. Based on microstructural evolution, hydration heat, hydration product composition, and pore structure, the modification mechanism of NSP and MSP on cement-based composites were investigated. The results show that adding NSP improves the fluidity of cement-based composites while adding MSP has the opposite effect. An appropriate amount of MSP and NSP improves the durability of cement-based composites. However, both NSP and MSP reduce the 28d strength of cement-based composites. Compared with NSP, the incorporation of MSP reduces the hydration release rate, refines the pore structure, and improves the interface bond with the cement matrix. This study deepens our understanding of the influence of SP on the fundamental properties of cement-based composites, which also provides new perspectives on creating a sustainable built environment.